1972
DOI: 10.2307/1935707
|View full text |Cite
|
Sign up to set email alerts
|

Competition, Predation, and the Structure of the Ambystoma‐Rana Sylvatica Community

Abstract: Populations of six species of amphibians were manipulated in field enclosures to study the biological tractability of current concepts of . the organization of natural communities. Experimental communities with a known composition of mature eggs were introduced into screen enclosures in a pond to assay the importance of competition and predation to the ecology of amphibian larvae in temporary ponds. The competitive ability of each population was measured by its survivorship, mean length of its larval period, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
372
1
3

Year Published

1980
1980
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 377 publications
(396 citation statements)
references
References 91 publications
(116 reference statements)
20
372
1
3
Order By: Relevance
“…41-43). It has long been known that characterizing the net effects of interactions in multispecies communities entails understanding the direct and indirect effects of those species on one another (44,45). However, natural selection acts on lifetime fitness, and the fitness of long-lived mutualists is determined by the temporally integrated effects of multiple partners.…”
Section: Discussionmentioning
confidence: 99%
“…41-43). It has long been known that characterizing the net effects of interactions in multispecies communities entails understanding the direct and indirect effects of those species on one another (44,45). However, natural selection acts on lifetime fitness, and the fitness of long-lived mutualists is determined by the temporally integrated effects of multiple partners.…”
Section: Discussionmentioning
confidence: 99%
“…Few partial migration studies on vertebrates, however, have shown density effects using replicated field experiments, probably because of the difficulties of enclosing wide-ranging animals. However, density effects are well known in the ecological literature, documented in topics ranging from dispersal to metamorphosis, disease, and phenotypic plasticity (e.g., Wilbur 1972, Matthysen 2005. Most commonly, environments under increasing density induce change in individuals, ranging from changes in habitat to spatial location, diet, behavior, or phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that growth and survival are density-dependent with competition for food being one of the most important factors (Brockelman, 1969;Wilbur, 1972Wilbur, , 1976. Differential growth rates may not only contribute to unequal competitive abilities but also appear to affect predation risk (SmithGill and Gill, 1978;Wilbur, 1980).…”
Section: Introductionmentioning
confidence: 99%